PENGARUH STRATEGI PEMBELAJARAN MODELLING THE WAY TERHADAP PEMAHAMAN KONSEP SISWA KELAS V PADA PEMBELAJARAN IPAS DI SD - Hajizah, Siti; Erdi Guna Utama; Sri Mulyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims: 1) to determine the difference in students' concept understanding between classes that apply the modeling the way learning strategy and classes that do not apply the modeling the way learning strategy; 2) to determine how much influence the modeling the way learning strategy has on the concept understanding of grade V students in IPAS learning in elementary school; 3) to determine the implementation of the use of the modeling the way learning strategy in IPAS learning in grade V elementary school. The type of research used is quantitative research with Quasi Experimental Design and Posstest-Only Control Group Design form. The population in this study were grade V students of SDN 26 Singkawang, totaling 47 people. The data collection technique used test and non-test techniques where the test technique was in the form of essay questions containing indicators of concept understanding and non-test techniques in the form of an implementation observation sheet containing the syntax of the modeling the way learning strategy. Data analysis techniques using t-test and Effect Size. The results showed that: 1) There is a difference in students' concept understanding between classes that apply the modeling the way learning strategy and classes that do not apply the modeling the way learning strategy with the results of tcount> ttable, namely 4.176> 2.021. 2) Modeling The Way Learning Strategy has a great influence on the understanding of the concept of grade V students in learning IPAS SD 26 Singkawang. This is indicated by the calculation of the Effect Size value of 1.20 which is in the high criteria. 3) The use of the Modeling The Way strategy is well implemented in IPAS learning in class V. So that there is an effect of the modeling the way learning strategy on the understanding of the concept of grade V students in IPAS learning in elementary school.